Intraspecific resource partitioning by Hampala macrolepidota(Van Hasselt) in lotic and lentic environment of Kenyir reservoir, Malaysia - Chowdhury, Ahmed Jalal Khan (Fakulti Perikanan dan Sains Samudera, 2010)
A study of Iniraspecific Resource Partitioning on a tropical sport fish 'Side bar barb' Hampala macrolepidota van Hasselt. was carried out in lotic and lentic habitat at Kenyir Reserv oir, Terengganu, Malaysia.Physico-chemical regimes of Kenyir Reservoir were also studied to determine the species ecological requirements. The water quality data showed that Kenyir Reservoir is suitable for fish culture. The most vital ecological factors, temperature and dissolved oxygen levels, were within the acceptable range for fish until 10.0 m depth. Waterlevel and rain fall both showed significant (P<05) effects on the availability offish in both habitats.